RESEARCH OF GENDER-BASED BEHAVIOURAL DIFFERENCES IN THE PURCHASING DECISION-MAKING PROCESS - Dijana Tevšić; Arnela Nanic (Economic Review)
The goal of this paper is to explore changes in consumer behavior which were caused by mo-dern consumer trends with the accent on gen-der-based differences in behavior by purcha-sing process. Consumer behavior in the pur-chasing process depends on a great number of factors, and one of them is certainly the gender of consumer. Shopping habits and gender-based consumer attitudes are significantly different and have changed during the past several yea-rs. With the arrival of new technologies and the usage of modern marketing tools, these gender-based differences are remarkably changing. The habits of men and women during pur-chasing decision-making processes have comp-letely new characteristics now. It is very difficult to gain consumers' trust in time when they can easily access a great amount of information in every moment and producers must invest a greater effort to please every need of modern and informed consumers. The aim of this paper is to analyze the considerable differences in shopping behavior of both male and female, to research their attitudes and habits by purchasing decision-making process and to determine new shopping trends of these consumer categories. Using a structured survey questionnaire in this paper the key differences will be explored of gender-based consumers presenting themselves in the purchasing decision-making process as well as their habits and styles.